A Simple Intermolecular Model Used to Study Interfaces - Filino Harahap (Journal of Mathematical and Fundamental Sciences, 1971)
Flachsbart and Anliker (1) used a simple molecular model to study the effect of gravity on the contact angle and the interface shape. Here, the problem is extended by considering the solid body rotation of a constant volume liquid in a pan. The effect of the centrifugal body force is included in an attempt to study dynamic effects on the contact angle. It was found, that the contact angle is not dependent upon the included body forces as far as the order of approximation of the analysis is concerned. The microscopic structure of the gas-liquid interface, which is involved in the problem considered, the structure of the surface tension and the contact angle are presented.